(untitled) (INNOVATIVE ECONOMY, 2020)
Somchenko V.V., Kondratenko A.I. STUDY AND ANALYSIS OF THE MAIN TENDENCIES AND SPECIFIC FEATURES OF INFLATION PROCESSES IN UKRAINE AND EU COUNTRIES IN 2008-2017 Purpose. The aim of the article is the study and analysis of the main tendencies and specific features of inflation processes in Ukraine and EU countries in 2008-2017, development of practical recommendations on the mechanism of their regulation. Methodology of research. The following methods and techniques are used for the realization of the tasks: monographic – for a comprehensive study of the main tendencies and specific features of the inflation processes in Ukraine and the EU; dynamic series analysis and graphic method are used to illustrate the change in the inflation rate in Ukraine. Findings. The indicators of inflation in Ukraine and EU countries in 2008-2017 are considered and analyzed. It is found that today inflation is peculiar to all countries of the world. The main causes and factors of influence on inflation processes in the modern market economy are determined. It has been established that inflation is one of the main destabilizing factors, especially in transition economies. It is investigated using the consumer price index, which is most often used as an indicator of inflation processes, the dynamics of inflation in Ukraine, the Eurozone, the Czech Republic, Poland, Sweden and the United Kingdom over the last decade. The types of inflation in the studied countries in 2008-2017 are determined. The peculiarities of inflation processes in Ukraine and EU countries are established. The consequences of inflationary processes in Ukraine are determined. The common and distinctive features of inflation processes in Ukraine and EU countries are revealed. It is determined that their energy dependence is one of the main factors of inflation in the studied countries. It is substantiated that since in the modern world inflation is a chronic and comprehensive phenomenon that can not be completely eliminated in market conditions, it is an important task of the state to take effective measures for its regulation in the form of anti-inflationary policy. The peculiarities of anti-inflationary policy in the EU countries that should serve are investigated. Scientific novelty. It is proved that the main methods and instruments of the monetary policy of the European Central Bank during the investigated period are interest rate and asset redemption programs. The recommended anti-inflation measures are set for more effective regulation of inflation processes in Ukraine. It has been established that the main means of combating inflation is to overcome its main causes, among which important importance is devoted to the introduction of effective monetary policy, namely the regulation of interest rates and money supply in the country. Practical significance. The obtained results of the study are aimed at solving the problems of inflation in our country, namely the use of effective control over the inflation process and the identification of effective measures to reduce it. Key words: inflation; causes of inflation; trends; inflationary processes; anti-inflationary measures.